Psoriasis is associated with risk of obstructive sleep apnea independently from metabolic parameters and other comorbidities: a large hospital-based case-control study. - Papadavid, Evangelia; Dalamaga, Maria; Vlami, Katerina; Koumaki, Dimitra; Gyftopoulos, Sotirios; Christodoulatos, Gerasimos Socrates; Papiris, Spyridon; Rigopoulos, Dimitrios (Sleep Breath, 2017)
PURPOSE: Obstructive sleep apnea (OSA) represents a breathing disorder during sleep with significant health consequences. Few studies have examined the prevalence of OSA in psoriatic patients and whether OSA may be associated with psoriasis risk. We aimed to explore: (1) the inverse relationship, that is whether psoriasis might represent an independent predictor of OSA and its severity considering important predisposing factors and (2) the psoriatic phenotype related to severe OSA. METHODS: In a large hospital-based case-control study, we examined a total of 253 patients with OSA and a control group of 104 subjects without OSA, who underwent full nocturnal polysomnography and dermatologic examination. RESULTS: The prevalence of psoriasis was significantly greater in OSA patients than in controls (p = 0.03). Psoriasis was associated with OSA risk (p = 0.04) but not severity of OSA, sleepiness severity or sleep efficiency, independently from age, gender, anthropometric features, and significant comorbidities. The phenotype of a psoriatic patient suffering from severe OSA is not different from that of a patient with severe OSA and is not associated with psoriasis severity indexes. OSA psoriatic patients were not compliant with CPAP treatment in comparison with OSA patients without psoriasis. CONCLUSION: Psoriasis may represent an independent risk factor for OSA above and beyond significant comorbidities, anthropometric and metabolic parameters. Physicians should be aware of the bi-directional association of psoriasis and OSA. Managing psoriasis may be a potential target for preventing OSA as well as the potential cardiovascular mortality related to OSA and psoriasis.